Potassium, uranium and thorium geochemical maps of the conterminous USA - J. S. Duval (The Institute of Materials, Minerals and Mining, 1991)
Paper presented at the 28th International Geological Congress held in Washington DC, July 1989 (International geochemical mapping sessions). The compilation of the National Uranium Resource Evaluation aerial gamma-ray data to produce maps of the apparent surface concentrations of potassium, uranium and thorium for the conterminous USA has resulted in a reasonably accurate representation of the distribution of these elements in the surface rocks and soils. This claim is supported by the general agreement between the mapped geology and the patterns seen in the data